An Ion-exchange Bone Demineralization Method for Improved Time, Expense, and Tissue Preservation. (September 2020) - Narotzky, Emma; Jerome, Maria E.; Horner, John R.; Rashid, Dana J.
Here, we describe an ethylenediaminetetraacetic acid (EDTA)-based bone demineralization procedure that uses cation-exchange resin and dialysis tubing. This method does not require solution changes or special equipment, is faster than EDTA alone, is cost-effective, and is environmentally friendly. Like other EDTA-based methods, this procedure yields superior tissue preservation than formic acid demineralization. Greater protein antigenicity using EDTA as opposed to formic acid has been described, but we also find significant improvements in carbohydrate-based histological staining. Histological staining using this method reveals cartilage layers that are not distinguishable with formic acid demineralization. Carbohydrate preservation is relevant to many applications of bone demineralization, including the assessment of osteoarthritis from bone biopsies and the use of demineralized bone powder for tissue culture and surgical implants. The improvements in time, expense, and tissue quality indicate this method is a practical and often superior alternative to formic acid demineralization: